Handbook of regional growth and development theories - Capello, Roberta; Nijkamp, Peter (Cheltenham, UK; Northampton, MA : Edward Elgar, 2009)
The book covers topics in regional growth and development policies and measurement methods; development theories of innovation, knowledge and space, regional production factors; and growth theories and space. The focus is to collect cutting-edge theories explaining regional growth and local development.
Includes bibliographical references and index.
rua 07/02/14
Loans
Keywords: Regional economics; Economic development; Regional economics